Recent Development of Printed Micro‐Supercapacitors: Printable Materials, Printing Technologies, and Perspectives. Issue 3 (3rd April 2019) - Li, Hongpeng; Liang, Jiajie
Abstract: The rapid progression of portable and wearable electronics has necessitated the development of high‐performing, miniaturized energy‐storage devices with flexible form factors and high energy and power delivery. Printed micro‐supercapacitors (MSCs), with in‐plane interdigital configurations, is touted as a promising choice to fulfill these requirements. New printing technologies can assemble MSCs with fiscal and environmental benefits, large form factors, and at high throughputs, qualities not afforded with conventional microfabrication technologies. Here, recent progress in the preparation of functional ink systems for wearable MSCs, encompassing electrode materials, conductor materials, and electrolytes, is presented. First, a comprehensive background of the fundamentals of printing technology is introduced, with discussions focusing on methods of improving ink functionality while simultaneously retaining good printability. Second, various printing techniques to ensure manufacturable scaling of wearable MSCs with high areal electrochemical performance and small footprint are explored. Within the scope of these two topics, various issues that hinder the full materialization of widespread adoption of printed MSC and next steps to overcome these issues are discussed. Further deep dives in scientific and technical challenges are also presented, including limited functionality of the inks, low printing resolution, overlay accuracy, and complex encapsulation. Abstract : Printed micro‐supercapacitors, with in‐plane interdigital configurations created by printing technology, have been touted as a promising miniaturized energy‐storage device to provide a continuous power supply to drive wearable on‐chip integrated electronics. Critical printable materials and printing techniques are presented to push forward the full materialization of widespread adoption of printed micro‐supercapacitors.